MORPHOLOGICAL RESPONSE OF OIL PALM (ELAEIS GUINEENSIS JACQ.) IN SOCFINDO DXP YANGAMBI (Y) SEEDS AGAINST SALINITY STRESS AT THE PRE NURSERY STAGE - Fadly Himawan; Eka Bobby Febrianto; Sri Murti Tarigan; Wagino (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Abstract Salinity stress is one of the environmental factors that can affect the growth and development of oil palm, particularly during the nursery stage. This study aimed to evaluate the morphological responses of oil palm (*Elaeis guineensis* Jacq.) seedlings of the Socfindo DxP Yangambi (Y) variety to different salinity levels during the *pre nursery* stage. The experiment was conducted in the greenhouse and laboratory of the Indonesian Oil Palm Institute of Technology (ITSI), Medan, using a Randomized Block Design with one factor consisting of three salinity treatments, namely S0 (0 mmhos), S1 (5–6 mmhos), and S2 (6–7 mmhos), with three replications. The observed parameters included plant height, stem diameter, number of leaves, chlorophyll content, root volume, shoot volume, root length, shoot length, root fresh weight, shoot fresh weight, root dry weight, and shoot dry weight. The results showed that salinity treatment had no significant effect on plant height, stem diameter, number of leaves, chlorophyll content, shoot volume, root length, shoot length, root fresh weight, shoot fresh weight, root dry weight, and shoot dry weight. However, salinity significantly affected root volume, with the highest value obtained under the S1 treatment (5–6 mmhos), reaching 0.67 cm³. The results indicate that oil palm seedlings of the Socfindo DxP Yangambi (Y) variety possess good adaptability to salinity stress up to 7 mmhos during the *pre nursery* stage.